Developing a GRI-G4-based persuasive communication framework for sustainability reporting (SR): Examining top 10 Indian banks. Issue 1 (15th January 2018) - Kumar, Ranjan; Pande, Neerja; Afreen, Shamama
Abstract : Purpose: The purpose of this paper is to critically examine sustainability reporting (SR) practices of top 10 Indian banks, on parameters derived from a Global Reporting Initiative (GRI)-G4-based persuasive communication framework. Design/methodology/approach: SR metrics from GRI-G4 guidelines were mapped to persuasive communication parameters to develop a blended analytical framework. Content analysis (CA) technique was used to assess SR of top 10 banks on this framework. Findings: The study has three key findings. First, most of the top 10 Indian banks are yet to adopt adequate disclosure and transparency practices in SR. Second, even though environmental and social goals are broadly reported, there are glaring omissions on metrics like "equal remuneration, " "occupational health and safety" and "customer privacy." Third, stakeholder engagement focus is weak as reflected in low persuasive appeal of SR content of most banks. Research limitations/implications: The blended framework provides a theoretical and analytical pathway for operationalizing the sustainability context principle, which has been inadequately addressed even within the GRI framework implementation. Practical implications: The paper provides a "health check" and identifies "red flags" in SR of top 10 Indian banks, enabling them to undertake a critical review of their sustainability metrics and reporting practices. Social implications: The paper establishes the significance of evaluating non-financial reporting practices addressing broader sustainability metrics in the banking sector, in an emerging economy context. Originality/value: This paper develops a GRI-G4-based persuasive communication framework for SR assessment, and conducts an evaluation of top 10 Indian banks using CA technique.